What determines the position of regions in European knowledge networks? A comparative perspective on R&D collaboration, co-patent and co-publication networks - Iris Wanzenböck; Thomas Scherngell; Thomas Brenner (European Regional Science Association (ERSA), 2013)
The question of why certain regions are more efficient in creating new knowledge is one of the main research issues in Regional Science. In the recent past, inter-regional knowledge networks ? defined as the inter-linkage of collaborative endeavours in knowledge creation across regional boundaries ? have been increasingly considered as important element for knowledge generation processes. Such inter-regional knowledge networks may constitute promising channels to tap knowledge that is widely dispersed in geographical space. This paper investigates the position of regions in inter-regional knowledge networks at the European level, taking a comparative perspective on the R&D collaboration network as given by the European Framework Programmes (FPs), the co-patent network and the co-publication network. The aim is to identify how region-specific and spatial factors explain positioning in European knowledge networks. In order to take account of structural properties of each network type, we apply a Social Network Analysis (SNA) perspective, defining a region?s network position in terms of its centrality according to inter-regional collaboration intensities. By this, we use eigenvector centrality, placing the region in a central hub position, and betweenness centrality, assigning central regions the ability to control knowledge diffusion in the network. In modelling network centrality we distinguish between regional characteristics that reflect a region?s knowledge production capacities (capacity dimension), and the variety in a region?s knowledge production activities (relational dimension). Our empirical model specification in form of a mixed effects panel version of the Spatial Durbin Model (SDM) allows accounting for the spatial autocorrelation in explaining network position by differentiating between direct, region-internal, and indirect, region-external impacts arising from our set of explanatory characteristics. The results provide first empirical evidence on regional factors that influence position in inter-regional knowledge networks from a comparative perspective on three different network types, given their distinct network structure in relational as well as spatial terms. The results reveal that internal capacity- and technology-related aspects but also spatial spillover impacts from surrounding regions prove to be particularly important for centrality in the co-patent network. We also find significant ? region-internal and region-external ? impacts of general economic conditions on a region?s centrality in the FP network. However, we cannot observe substantial spillover effects of region-external factors on centrality in the co-publication network. Thus, the distinctive knowledge creation foci in each network seem to find expression in its regional determinants.
Keywords: L14; N74; O33; R15; 330; knowledge networks; network position; network centrality; regional knowledge production; panel Spatial Durbin model